Efficacy and safety of lenvatinib plus transarterial chemoembolization with or without programmed death-1 inhibitors in the treatment of intermediate or advanced hepatocellular carcinoma: a systematic review and meta-analysis - Lei, Yongfa; Liang, Xiaotian; Zhu, Hua; Wang, Jin; Zhang, Xiaochen; Duan, Siliang; Liang, Weiming (Frontiers in Immunology, 2025)
IntroductionThis meta-analysis aimed to evaluate the efficacy and safety of Lenvatinib plus transarterial chemoembolization with or without programmed death-1 inhibitors (PD-1 inhibitors) in the treatment of intermediate or advanced hepatocellular carcinoma (HCC).Materials and MethodsFour databases (Pubmed, Embase, Web of Science, and Cochrane Library) were searched for studies comparing lenvatinib plus transarterial chemoembolization with PD-1 inhibitors (TACE-L-P) versus Lenvatinib plus transarterial chemoembolization (TACE-L) for intermediate or advanced HCC. Meta-analyses were conducted for progression-free survival (PFS), overall survival (OS), objective response rate (ORR), disease control rate (DCR), and Grade ≥ 3 treatment-related adverse events (Grade ≥ 3 AEs).ResultsThe meta-analysis comprised 19 retrospective cohort studies, including of 2002 patients diagnosed with intermediate or advanced HCC. In this cohort, 1011 individuals were administered TACE-L-P, while 991 patients received TACE-L. In comparison to TACE-L, TACE-L-P demonstrated a superior ORR [odds ratio (OR) = 2.38, 95% confidence interval (CI) 1.98 ~ 2.87, P < 0.00001] and DCR (OR = 3.22, 95% CI, 2.32 ~ 4.45, P < 0.00001). TACE-L-P showed superior efficacy compared to TACE-L regarding PFS (HR: 0.56, 95%CI 0.50 to 0.62, P<0.0001) and OS (HR: 0.70, 95%CI 0.60 to 0.80, P<0.0001). Regarding safety, the incidence of Grade ≥ 3 AEs was more prevalent in the TACE-L-P group compared to the TACE-L group (OR=1.58, 95% CI: 1.27 ~ 1.97, P<0.0001).ConclusionsThe present meta-analysis present a comparison of the efficacy and safety of TACE-L-P against TACE-L for intermediate or advanced HCC. TACE-L-P enhanced ORR, DCR, PFS, and OS relative to TACE-L. Furthermore, the improved efficacy of TACE-L-P was correlated with a rise in the incidence of Grade ≥ 3 AEs.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42024590414, identifier CRD42024590414.